Answer:
34.6 m/s
Step-by-step explanation:
Since there are no external forces acting on the system, the total momentum of the kids+sled system must be conserved, so we can write:
![p_i = p_f\\(m_A + m_B +m_C)u = (m_B + m_C)v](https://img.qammunity.org/2021/formulas/physics/middle-school/vkyedga6a3izm5oqiga5y5h7rd8cbb2m7m.png)
where:
is the mass of kid A
is the mass of kid B
is the mass of kid C
u = 19.8 m/s is the initial velocity of the system
v is the final velocity of the system, after kid A jumped off it
Here we have ignored the mass of the sled since it is not given.
Therefore, by solving the equation for v, we find the new velocity of the sled:
![v=(m_A + m_B + m_C)/(m_B +m_C)u=(42.8+31.5+25.9)/(31.5+25.9)(19.8)=34.6 m/s](https://img.qammunity.org/2021/formulas/physics/middle-school/ldmkp44d98hym8gelxr25nxv5tydjn4x3m.png)